THE INFLUENCE OF STUDENT TEAM ACHIVEMENET (STAD) TO THE STUDENTS’ LEARNING OUTCOMES IN CIVICS SUBJECT AT CLASS X OF STATE SENIOR HIGH SCHOOL 7 BINJAI - Heryansyah Ginting Ginting (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to determine the effect of STAD cooperative learning model on student learning outcomes in Civics subjects in class X SMA Negeri 7 Binjai. The problem identification in this research is the lack of student’s interest in the subject matter, this is because in general the Civics subject uses lecturing and rote method, lack of facilities for Civics subjects, and low student learning outcomes. The formulation of the problem in this research is whether there is influence of Cooperative STAD learning model on student learning outcomes in Civics subject. The type of research used in this study is experimental research. While the method used is quantitative method. Hypothesis in this research is there is influence of STAD type cooperative learning model to student learning result in civics (PPKn) subject. The population in this study amounted to 36 people and the sample in this study amounted to 20 people who said population samples taken by using simple random sampling technique or taking sample members of the population conducted randomly. The average value of the pretest result of students is 56.75 with a standard deviation of 282.30. And for the average value of posttest result of student equal to 77, 75 with standard deviation 1296, 11. From result of calculation of hypothesis test got r_h = 2, 48 and r_t lies 0,444. So there is influence of Cooperative STAD learning model on student learning outcomes in the eyes of Civics class X SMA 7 Binjai. With r_ (count) (2.48) and r_tabel (0.444). With t_ (count)4.65> 1.73. From r_ (table) it shows that there is influence between two variables